Development of a composite substrate peel test to assess moisture sensitivity of aggregate–bitumen bonds - Zhang, Jizhe; Airey, Gordon D.; Grenfell, James; Apeagyei, Alex K.; Barrett, Martyn (Elsevier, 2016)
This paper presents the development of a suitable procedure to prepare peel test specimens using coarse aggregates and compare the results with the established standard peel test. The newly developed composite substrate peel test (CSPT) was found to be effective in characterising the moisture sensitivity of the aggregate–bitumen bond and the results correlated well with the results from a standard peel test. The results from the CSPT and the standard peel test showed that the fracture energy after moisture damage was found to be aggregate type dependent. Limestone tends to have better resistance to moisture damage than granite when moisture adsorptions are similar. Furthermore, in terms of similar aggregates, lower moisture adsorption results in better moisture resistance. This phenomenon suggests that in a moisture susceptible asphalt mixture, the effect of aggregate may be more influential than the effect of bitumen. Strong correlations were found between the standard peel test and the CSPT in terms of moisture damage evaluation and suggest that the CSPT maybe a more practical procedure to test the aggregate–bitumen bond for actual aggregates used in asphalt mixtures.